Injuries in racket sports among Slovenian players - Kondric, M.; Matkovic, B.; Furjan-Mandic, G.; Hadzic, V.; Dervisevic, E. (Collegium Antropologicum, 2011)
On the sample of 83 top Slovenian athletes we have studied the frequency of injuries among table tennis, tennis and badminton players, types of injuries and severity of injuries - the latter based on data of players absences from training and/or competition processes. The most liable parts to injuries are shoulder girdle (17.27%), spine (16.55%) and ankle (15.83%), while foot (10.07%) and wrist (12.23%) are slightly less liable to injuries. The most frequent injuries in racket sports pertain to muscle tissues. According to this data, the majority of injuries occur halfway through a training session or a competition event, mostly during a competition season. The injuries primarily pertain to muscle tissues; these are followed by joint and tendon injuries. There are no differences between male and female players. Compared to other racket sports players, table tennis players suffer from fewer injurie